PERTUSSIS - Dhea Asty Ramadhani (Yayasan Pendidikan Medika Indonesia, 2025)
Pertussis or whooping cough is a respiratory infection caused by the bacterium Bordetella pertussis and remains a global health problem. The WHO reported 139,786 cases of pertussis in 2014 shows that the disease continues to pose a significant public health threat. Pertussis has three phases of clinical manifestation, namely catarrhal, paroxysmal, and convalescent phases. The diagnosis can be established through DFA, culture, and PCR tests. Its management includes pharmacological therapy with antibiotics (azithromycin, erythromycin, clarithromycin) and non-pharmacological interventions. Complications can affect the respiratory, digestive, circulatory, urinary, and nervous systems, with the highest severity observed in infants and parents. Pertussis remains a significant infectious disease with the potential for serious complications, especially in extreme age groups. Early diagnosis and proper management are essential to prevent complications and reduce mortality.